BETWEEN MIND AND HEART: FROM HUMANISTIC PSYCHOLOGY TO EMOTIONAL INTELLIGENCE (Psychology Travelogs, 2025)
The article explores the philosophical and psychological evolution that redefined emotion as a vital dimension of human intelligence in the mid-twentieth century. Thinkers such as Abraham Maslow, Carl Rogers, Rollo May and others transformed psychology into a discipline concerned not only with pathology but with authenticity, meaning, and growth. Together, they established the conceptual and ethical foundations for what would later be called emotional intelligence – the integration of thought and feeling, cognition and compassion, reason and value. The article argues that emotional intelligence should not be seen as a contemporary innovation but as the culmination of a humanistic tradition that redefined intelligence as the harmony between mind and heart, between knowing and caring, between awareness and empathy – the moral essence of what it means to be human.
Keywords: emotion; mind; empathy; emotional intelligence; heart